Banking regulators (Oxford [U.K.] ; New York : Oxford University Press, 2006)
This publication provides detailed, consistently presented information for some 300 institutions globally. It covers organizations with regulatory responsibilities, whether primary or secondary, for the banking sector on both national and international levels.
osa11/06/13
Loans
Keywords: Banking law; Independent regulatory commissions; Global financial services regulation; Banks and banking